Synthesis of Graphene Oxide/Polypyrrole (GO/PPy) from Used Batteries as Electrodes in Supercapacitor Cells - Muhammad Iqbal Qeis; Ferdian Rizki Amanda; Desi Listiani; Anthoni B Aritonang; Intan Syahbanu (Jurnal Kimia Valensi, 2019)
Fabrication with graphite-modified GO/PPy composites have been studied from used batteries using the Hummers method. This research was performance in four steps: graphite powder preparation, GO synthesis, GO/PPy composite synthesis, and supercapacitor cell manufacturing. The results of the study were characterized using X-Ray Diffraction (XRD) to see the character of the diffraction patterns formed by carbon batteries used before and after calcination and Fourier Transform Infra-Red (FTIR) to identify compound functional groups and conduct initial tests in the form of voltage, capacitance and life cycle by measuring charge and discharge times. The graphite preparation stage is carried out by the calcination method at 900°C to produce graphite with an angle of 2θ which is 26° with reflection from (d002). FTIR data showed that GO/PPy composites showed a successful combination of characteristics similar to pure polypyrrole and GO which included a broad absorption band located at 3500-2300 cm-1 which was estimated to be stretching the amine from polypyrrole and O-H group in the GO layer and the emergence of peaks new in the absorption band with a wave number 909 cm-1 is the CN vibration of the polymerized pyrrole. Meanwhile, based on the LCR meter measurement results in the best supercapacitor cells in the sampel GO/PPy ratio (3:10) with voltage value of 74.1 mV; a capacitance value of 15.14 µF and the best charge and discharge times.